2004
DOI: 10.1081/ceh-120027328
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of Exogenous Angiotensin II on Plasma Fibrinolytic Balance in Normal Subjects

Abstract: In conclusion, in healthy volunteer subjects, short-term infusion of Angiotensin II without and with concomitant administration of an AT1-receptor antagonist has no effect on PAI-1 activities and plasma concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
8
1
2
Order By: Relevance
“…Hence, it is often claimed that elevated Ang II is associated with increased PAI-1. In contrast, studies by others and us show decreased PAI-1 during Ang II infusion [17,18]. Although it cannot be ruled out that Ang II may stimulate PAI-1 production in the longterm setting, we found no short-term effect of Ang II on circulating PAI-1.…”
Section: Discussioncontrasting
confidence: 81%
“…Hence, it is often claimed that elevated Ang II is associated with increased PAI-1. In contrast, studies by others and us show decreased PAI-1 during Ang II infusion [17,18]. Although it cannot be ruled out that Ang II may stimulate PAI-1 production in the longterm setting, we found no short-term effect of Ang II on circulating PAI-1.…”
Section: Discussioncontrasting
confidence: 81%
“…Some reports have suggested that AT 1 receptor antagonists have no effect on PAI-1 activity and fibrinolysis in healthy subjects and patients with mild hypertension [19,20]. It is of interest that candesartan treatment reduces PAI-1 expression in spontaneously hypertensive rats, but has no effect in Wistar-Kyoto rats [6] and that AT 1 receptor blockers reduce PAI-1 activity in hypertensive patients [8]; these results suggest that the effect of AT 1 receptor antagonists on fibrinolytic balance may only be of importance in a pathologic state.…”
Section: Discussionmentioning
confidence: 98%
“…A first study in vivo, in which four normotensive subjects and six hypertensive patients received an intravenous infusion of angiotensin II demonstrated a rapid increase in circulating levels of PAI-1 [Ridker et al 1993]. However, other study groups were unable to confirm an increase in PAI-1 levels in response to angiotensin II infusion or following ARB treatment (Figure 3) [Lottermoser et al 2000[Lottermoser et al , 2004Skurk et al 2004].…”
Section: Is There Evidence Of Effects Beyond Bp Lowering?mentioning
confidence: 99%